PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PDEODE (PREDICT DISCUSS EXPLAIN OBSERVE DISCUSS EXPLAIN) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI MIPA SMAN 3 PEKANBARU - Devi Raini; R. Usman Rery; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purposes of this research are to improve student achievement and to know the effect of implementing learning model of cooperative PDEODE (Predict Discuss Explain Observe Discuss Explain) on the balanced chemical subject in the class XI MIPA SMAN 3 Pekanbaru. This experiment research using Design Randomized Control Group Pretest-Posttest. The research sample consisted of two class, class XI MIPA 2 as experiment class and class XI MIPA 4 as control class that has tested by normality test using Liliefors test and homogeneity test using equality of two average test. Hypothesis was done by using test-t right side. Research result shown that the implementation of learning model of cooperative PDEODE (Predict Discuss Explain Observe Discuss Explain) can improve student learning achievement on the balanced chemical subject where tarithmetic = 2,23 > ttable = 1,67.Key Words: Learning Model Of Cooperative PDEODE (Predict Discuss Explain Observe Discuss Explain), Learning Achievement, Balanced Chemical